Towards a spatial decision support system for route alignment planning in Egypt - Ahmed Talaat (European Regional Science Association (ERSA), 2002)
Route alignment planning for a new highway or railway on the regional level constitutes a complicated planning process which involves the consideration of various data sets and the analysis of such data. It also involves the development of alternative corridors for the potential road and the evaluation of socioeconomic and environmental impacts of such alternatives. The comparison of produced alternatives is another complicated task. In Egypt, and particularly in the General Authority for Roads, Bridges and Land Transport (GARBLT), those tasks are implemented traditionally using manual systems. The choice of a feasible corridor for a new high way is based solely on the topography of the land. The lack of cooperation between the different local authorities and ministries involved complicates the process of data acquisition, integration and analysis. Subsequently, historical, economical and geological data are not accurately considered. Environmental and social impacts are often neglected. To overcome such deficiency, the use of Geographic Information Systems (GIS) is mandatory to manage the variety of data sets coming from different sources. But before the introduction and application of GIS would be of any benefit to the GARBLT, some institutional changes are required to allow the data collection and exchange among the different authorities and ministries. The main objective of the present Ph.D. study is to demonstrate to the decision makers and transport planners in GARBLT the capabilities and functions of GIS in the field of route alignment planning and the benefits they will gain if they adopt a certain strategy for data acquisition and maintenance, in the hope that they will move towards a more scientific and up-to-date work methodology. The study will attempt to explore and demonstrate the potentials of the use of GIS in the route alignment planning process. It will also identify the information needs of the route alignment planning process and how it can be integrated and structured in a unified data model. The institutional measures needed for data exchange policies will also be recommended. As a means of achieving these objectives a spatial decision support system (SDSS) for the route alignment planning process will be designed and developed using GIS techniques and capabilities. Such a system should allow multi-criteria analysis and evaluation so that transport planner can come up with some alternative road corridors and evaluate the environmental, social, traffic and economic impacts of each corridor. The incorporation of such factors in the route alignment process is one of the additions to the current system which takes place in GARBLT. Another new aspect is the development of a system that can be reapplied several times as it is intended during the present study rather than aiming at finding the optimum route for a certain project as it is the case in most of the case studies in the literature. This paper explains the need for such a system in Egypt, describes the research plan and the methodology to be followed during this study and demonstrates the results obtained so far from the achieved stages namely the state-of-the-art and the analysis of the current system of route alignment planning in GARBLT.
Keywords: 330